Disease Diagnosis Using Tongue Image Analysis - Yogi Zulfadli; Arry Verdian; Muhammad Mamur (Proceeding International Conference on Information Technology and Business, 2017)
The tongue is an important part of human body to taste, speak and swallow the food. It reflect the inner working of body. Any kind of unusual behavior of body is reflected through tongue like problem in stomach, pancreas, liver and intestines etc. So in this paper, we are proposing automatic computer based technique to analyze the changes in tongue, which will be latter useful in diabetes diagnosis in patients. The main focus of our paper deals threshold of tongue signs for diagnosis the diseases. The sign classifies the tongue irregular shape, overlapping of colors, saliva on cracks, buds, pimples etc. Each signs have unique character reflections and issues. This sign factor consists of several phases; quantitative features texture measures for tongue image acquisition by using image processing and crack segmentation.Key Word: automatic computer based, threshold, image acquisition